Exploring the Potent Anti-Hyperglycemic Properties of Red Betel Leaf Ethanol Extract Fraction on Male Wistar Rats - Upi, Andi Ulfiana Utari; Aliah, Ahmad Irsyad; Hasniah; Basir, Nasrawati; Sadsyam, Sriyanty (Journal of Health Sciences and Medical Development, 2023)
Hyperglycemia is characterized by an increase in blood glucose levels exceeding 200 mg/dL, an initial symptom of diabetes mellitus. Hyperglycemia can be addressed through traditional treatment with Red Betel Leaf. Red betel leaf contains phytochemical compounds, including flavonoids. Flavonoid compounds in red betel leaves possess antioxidant properties. These antioxidants can scavenge hydroxyl radicals that damage the β cells of the pancreas, thereby maximizing insulin production. Empirically, the flavonoid content in red betel leaves has been shown to lower blood glucose levels and cure diabetes mellitus. An effectiveness test of the anti-hyperglycemic properties of the ethanol extract fraction of red betel leaf was conducted. This research aimed to determine the effectiveness of the ethanol extract fraction of red betel leaf on male white rats. The method employed in this study was laboratory experimentation. Fifteen rats were divided into five treatment groups: Group I, healthy control without treatment; Group II, negative control with Na.CMC administration; Group III, positive control with glibenclamide administration; Group IV, the polar group with polar extract suspension of red betel leaf administration; Group V, the nonpolar group with nonpolar extract suspension of red betel leaf administration. In conclusion, administering the polar fraction was more effective in reducing blood glucose levels than the nonpolar fraction.